Nasal myiasis in clinical practice - Santosh Kumar Swain; Mahesh Chandra Sahu; Manash Ranjan Baisakh (Apollo Medicine)
Nasal myiasis is an opportunistic parasitic infestation of human as well as animals. Infestation of the nasal cavity by dipterous larvae is called nasal myiasis which is commonly seen in developing countries where health and sanitation are poor. Different predisposing factors associated with nasal myiasis are atrophic rhinitis, diabetes with purulent nasal discharge, midline granulomatous lesions or malignancy, and poorly nourished patients with poor hygiene. Other possible predisposing factors causing nasal myiasis include neglected children, mental retardation, and elderly age. Nasal endoscopy is a better method for removal of maggots under direct vision. Nasal endoscopic method is a better technique for the removal of maggots than conventional manual method. The maggots which are often located in deep and inaccessible areas are easily identified and removed.